Analisa Gangguan Motor Close Cycle Cooling Water Pump (Cccwp ) #A Steam Turbin Menggunakan Vib Xpert Di Pltgu Grati - Moch Avif Romadhoni; Jamaaluddin Jamaaluddin (Muhammadiyah University, Sidoarjo, 2018)
PT Indonesia Power UPJP Perak Grati is the one state-owned enterprice (BUMN) which operates on an electricity power generation so that needed same assistance equipment for anufacturing, a 6 Kv induction motor, need to do a maintenance periodically for keeping the accomplishment. The author wrote te thesis to analize the motor disturbance Close Cycle Cooling Water Pump (CCCWP) #A Steam Turbine in order that there is no the suddenly disturbance in the motor equipment so that make the accomplisment of cooler system steam turbine disturbed. The method which doing the taking same data for motor vibration noise using vibxpert whict can analize the result and taking same data using motor current signature analysis (MCSA) functioned for analyzing the disturbed of the current and voltage. Based on the result, it can be concluded that vibrasi noise increase periodicly from bearing motor side there is a current data different becaused the outer part motor so that need doing a maintenance strategy so that the equipment remains reliable to operate.